Some Macrofungi Determined in Oltu and Narman (Erzurum-Türkiye) Region - Sadullahoglu, Cemil; Uzun, Yusuf (Kahramanmaras Sutcu Imam Univ Rektorlugu, 2025)
This study reports on macrofungus samples collected within the borders of Oltu and Narman (Erzurum) districts in 2018 and 2019. As a result of field and laboratory studies, 198 species were identified. The species identified in the region are distributed in 5 classes, 12 orders, 52 families, and 103 genera. 187 of the identified species are new to the research area. The species are listed with their habitat, locality, and edibility status.
Keywords: Macrofungi; Biodiversity; Mycobiota; Erzurum